Need Analysis of an Authentic Blended Assessment Model Oriented to Self-Directed Learning - M. Zaim; Atmazaki; Yulmiati; Alicia, Dona (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
In designing the course or part of the course such assessments, it is well-established to know the lecturers’ needs as the preliminary study. This study aims to investigate the lecturer’s needs regarding the assessment model for Basic Reading in higher education. The data were collected through interviews with three lecturers. The researchers used purposive sampling to select the participants from a private university in Padang City, West Sumatera, Indonesia. The data from the interview were analyzed qualitatively. It was found that the lecturers perceived that they needed to improve the quality of teaching and learning, especially in assessment. They need to implement an authentic blended assessment model oriented to self-directed learning in Basic Reading subject, because it helps students to be independent.